每日一题[2277]复数除法

求证:$\left((2a-b-c)+(b-c)\sqrt 3{\rm i}\right)^3=\left((2b-c-a)+(c-a)\sqrt 3{\rm i}\right)^3$.

解析    根据题意,有\[\left((2a-b-c)+(b-c)\sqrt 3{\rm i}\right)\left(-\dfrac 12-\dfrac{\sqrt 3}2{\rm i}\right)=(2b-c-a)+(c-a)\sqrt 3{\rm i},\]因此\[\dfrac{(2a-b-c)+(b-c)\sqrt 3{\rm i}}{(2b-c-a)+(c-a)\sqrt 3{\rm i}}=-\dfrac 12-\dfrac{\sqrt 3}2{\rm i},\]从而\[\dfrac{\left((2a-b-c)+(b-c)\sqrt 3{\rm i}\right)^3}{\left((2b-c-a)+(c-a)\sqrt 3{\rm i}\right)^3}=1,\]原命题得证.

此条目发表在每日一题分类目录,贴了标签。将固定链接加入收藏夹。

发表评论